Live animal ultrasonic evaluation of backfat thickness and loin-eye - L M Turlington; L R Corah; Dell M Allen; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1986)
Determination of backfat thickness and loin-eye area in swine is essential for continued genetic progress, and ultimately, pork product acceptance. Leaner, faster growing boars and gilts must be provided by seedstock suppliers to the commercial swine producer. Research information has consistently shown that lean, fast growing boars are more feed efficient. Since feed represents 60% to 75% of the total cost of production, any genetic improvement in feed efficiency would have a rapid payback to the commercial producer. Obviously, swine producers that utilize "lean value" marketing programs must have backfat and loin-eye area data on replacement boars, in order to take advantage of marketing opportunities.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Ultrasonic evaluation; Backfat thickness; Loin-eye